International Manual of Oncology Practice (iMOP) - Principles of Medical Oncology - de Mello, Ramon Andrade; Tavares, Álvaro; Mountzios, Giannis (Springer International Publishing : Imprint: Springer, 2015)
This textbook addresses themes ranging from the molecular issues of cancer sciences to clinical practice in medical oncology. It clarifies many topics, including molecular oncology, chemotherapy pharmacology and practical issues for clinicians. Systemic treatments in many areas of oncology feature, such as breast cancer, gastrointestinal, thoracic, urological oncology, head and neck tumors, bone tumors, sarcomas and palliative care. An excellent source for young physicians and researchers in the field of oncology, this book furthers understanding of medical oncology practice and facilitates professionals' treatment of cancer patients. It sets the direction for future research in the field, and will become the readers' regular working tool.